Association of PPAR-α Gene Polymorphism (rs4253778) with Osteoporosis in Postmenopausal Turkish Women - Şengül Tural; Amir Saghafian; Gamze Alaylı; Ercan Tural; Esra Tekcan (Galenos Yayinevi, 2023)
Objective:Osteoporosis is a multifactorial disease characterized by decreased bone mineral density and deterioration of the microstructure of bone tissue. The existence of various candidate genes affecting bone mass has been reported. In this study, we examined the relationship between PPAR-α gene intron 7 G>C (rs4253778) polymorphism and osteoporosis.Materials and Methods:The stud included 250 postmenopausal women (150 cases with osteoporosis and 100 postmenopausal healthy controls) mostly from the Central Black Sea Region. Peripheral blood samples were taken from the patient and control groups, and deoxyribonucleic acid isolation was performed using the kit methodology. Genotyping was performed by polymerase chain reaction - restriction fragment length polymorphism method. Statistical Package for the Social Sciences 20 program and chi-square analyzes were performed for statistical analysis.Results:Because of the study, while there was no statistical significant association between genotype distribution and osteoporosis, the C allele frequency was higher in the patient group and it was statistically significant (p=0.017).Conclusion:To our knowledge, this is the first study conducted in the Central Black Sea Region, Turkey. By expanding the study population and combining the results, more descriptive results regarding the susceptibility of polymorphic regions to osteoporosis can be obtained.